RESPON MASYARAKAT TERHADAP KEBERADAAN HUTAN KOTA KAOMBONA DI KELURAHAN TALISE KECAMATAMANTIKULORE SULAWESI TENGAH - Acong, Ahmad; Rachman, Imran; Hamka, Hamka (Universitas Tadulako, 2020)
Forests and forestry are very crucial in offering a positive contribution to the outcomes of environment, social and economy of people around the forest. Community empowerment around forests is needed to maximize environmental, social and economic outcomes. (Edwards et al., 2018). Urban forests are very challenging in preventing environmental damage which is very detrimental, andÂ also cause problems in terms of high maintenance costs, and damage to improved infrastructure. (Roy et al., 2012). The purpose of this research is to find out communities' responses to the Kaombona City Forest in Talise Village, Mantikulore District, Central Sulawesi. The method of this research is quantitative descriptive method, through the steps of collecting primary data and secondary data through the second data obtained from direct interviews from respondents and other supporting data such as data from the Talise Village Government and literature review, using pengslaan 5 - 3-1 (Likert scale method) it can be concluded which responses and understand the community discussing the City of Kaombona Forest. The result of findings shows that communities' responses to the City Forest of Kaombona Very high, while the facilities and infrastructure are very supported by the community / highly approved because of the level of education of the community around the City Forest of Kaombona is relatively high.Keywords: Social Management, Response of the Kaombona City forest community, Palu